2021
DOI: 10.12968/ajmw.2020.0007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experience and challenges of maternity waiting homes in Jimma, southwest Ethiopia

Abstract: Background Establishing maternity waiting homes is a key strategy to address the geographic barrier to obstetric care access among women living in rural areas. In Ethiopia, maternity waiting homes have been in use for several years, with a sharp increase in the number of such facilities recently. However, there is little empirical evidence detailing the experiences and challenges faced by women during the implementation of this initiative in Ethiopia. Methods This study used a multiple case study design with q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Furthermore, it allows healthcare providers to convey health-related information, such as newborn feeding, family planning, and immunization to pregnant women at MWH. It also gives pregnant women the chance to discuss their experiences with one another and adopt behaviors that are crucial for safe motherhood [21,31,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it allows healthcare providers to convey health-related information, such as newborn feeding, family planning, and immunization to pregnant women at MWH. It also gives pregnant women the chance to discuss their experiences with one another and adopt behaviors that are crucial for safe motherhood [21,31,36].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas other reported that physically, MWHs are available in some areas but do not provide all-encompassing services. As a result, women who planned to stay there were required to bring their food and basic household supplies from home, such as mattresses and kitchen utensils for the duration of their stay [14,21,31,35,36].…”
Section: The Physical Aspects Of Mwhs and Services Providedmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the important barriers of women's access to MWHs were household chores and the fact that their use of MWHs depends largely on male-partners’ decisions [ 5 , 6 ]. Given the patriarchal dominance, final decisions regarding MWH use in Ethiopia is mainly made by male-partners [ 7 ].…”
Section: Introductionmentioning
confidence: 99%